FAKTOR EKSPLOITASI KAYU RAMIN (GONYSTYLUS BANCANUS MIQ) - Marolop Sinaga; Dulsalam Dulsalam; Sampe Radja Simarmata (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
This investigation is carried out in the Central Kalimantan and West Kalimantan areas at three logging companies. The purpose of this investigation is to determine the exploitation factor for Gonystylus bancanus Miq.The knowledge of exploitation factor will help logging companies in the planning and control of production. The exploitation factor is the ratio of stem volume utilized to the stem volume that actually could be utilized. The latter represents part of the stem from its lowest point to its first branch. The part of stem considered utilized is that part which reached the log pond or other point for marketing.Exploitation waste in the areas of the forest companies observed ranges from 11.1% to 21.2%. This means that the exploitation factor ranges from 78.8% to 88.9%. The average of exploitation waste is 16.7%, consisting of parts from stumps 2.9% and parts from stems 13.8%, and hence the exploitation factor is 0.81.Exploitation waste can be kept at a minimum by better planning and improving skills of the workers. The exploitation factors among provincial regions and logging companies are not significantly. Among diameter class, however, they differ highly significantly. Therefore, the exploitation factor reported here should be used with great care.